Viabilitas Benih Kopi Arabika (Coffea arabica L.) terhadap Lama Perendaman Air Kelapa pada Media Tanam yang Berbeda Setelah Skarifikasi Mekanis - Nurihandayani Nurihandayani; Adnan Adnan; Risky Ridha (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The aim of this study is to determine the effect of the duration of young coconut water soaking and different growing media on the viability of Arabica coffee seeds after mechanical scarification, as well as to identify the interaction between these two factors. This research was conducted over a period of three months, from July to September 2023, at the Laboratory of the Faculty of Agriculture, Samudra University, Langsa City. The study was designed using a completely randomized design with a factorial pattern, consisting of two factors: (1) the duration of soaking in young coconut water, which included 4 levels: L0 = Control, L1 = 3 hours, L2 = 6 hours, and L3 = 9 hours; and (2) growing media, which included 3 levels: M1 = Soil: manure, M2 = Soil: manure: rice husk, and M3 = Soil: manure: cocopeat. The parameters observed in this study were maximum growth potential, germination rate, seedling height, root length, seedling fresh weight, and seedling dry weight. The results showed that the duration of soaking in young coconut water did not have any significant effect on all observed parameters. However, different growing media had a highly significant effect on maximum growth potential, germination rate, seedling height, root length, fresh weight, and dry weight of the Arabica coffee seedlings. The M1 treatment gave the best results for maximum growth potential, germination rate, seedling fresh weight, and seedling dry weight, while the M3 treatment provided the best results for seedling height and root length of Arabica coffee seeds. There was no interaction between the duration of young coconut water soaking and different growing media on all parameters of Arabica coffee seed viability.